2018
DOI: 10.1016/j.cytogfr.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 family cytokines: Key inflammatory mediators as biomarkers and potential therapeutic targets

Abstract: IL-6 is a critical cytokine in acute phase response and involved in the pathogenesis of several chronic inflammatory diseases including cancer. Studies have highlighted that levels of IL-6 and its family members can be useful for diagnosis, prognosis of relapse-free survival and recurrence. IL-6 family cytokines have been identified as cancer biomarkers through screening of inflammatory mediators in different fluids including saliva, serum, and bronchoalveolar lavage fluid (BALF). IL-6 can be modulated by chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 81 publications
3
130
1
Order By: Relevance
“…On the other hand, the highest tested BFO concentrations were able to reduce the IL-6 levels, showing that both samples have an anti-inflammatory response. IL-6 cytokine is a pro-inflammatory compound of the inflammation acute phase, responsible for activating the T-helper cells, for inhibiting the T regulatory cells, and for assisting the modulation of the adaptive immunological response 38 . It is also found at high levels in chronic inflammatory processes such as rheumatoid arthritis, osteoporosis, Crohn s disease and psoriasis 17,38 .…”
Section: Investigation Of the In Vitro Bullfrog Oil Anti-in Amma-mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the highest tested BFO concentrations were able to reduce the IL-6 levels, showing that both samples have an anti-inflammatory response. IL-6 cytokine is a pro-inflammatory compound of the inflammation acute phase, responsible for activating the T-helper cells, for inhibiting the T regulatory cells, and for assisting the modulation of the adaptive immunological response 38 . It is also found at high levels in chronic inflammatory processes such as rheumatoid arthritis, osteoporosis, Crohn s disease and psoriasis 17,38 .…”
Section: Investigation Of the In Vitro Bullfrog Oil Anti-in Amma-mentioning
confidence: 99%
“…IL-6 cytokine is a pro-inflammatory compound of the inflammation acute phase, responsible for activating the T-helper cells, for inhibiting the T regulatory cells, and for assisting the modulation of the adaptive immunological response 38 . It is also found at high levels in chronic inflammatory processes such as rheumatoid arthritis, osteoporosis, Crohn s disease and psoriasis 17,38 . In fact, the decrease on the IL-6 levels promoted by the BFO and the BFO-CV at the highest tested concentrations allow us to suggest a dose-dependent bullfrog oil anti-inflammatory effect.…”
Section: Investigation Of the In Vitro Bullfrog Oil Anti-in Amma-mentioning
confidence: 99%
“…response. [42] TNF-α and IL-6 from activated microglia have also been documented to lead to neuronal degeneration. [43] Our results showed that RV01 markedly suppressed TNF-α and IL-6 secretion and mRNA expression in LPS-stimulated microglia.…”
Section: Figurementioning
confidence: 99%
“…Our study also has implications for other chronic medical conditions including cancer. Music and EE-based interventions may serve as preclinical surrogate for developing adjunct digital therapeutics for cancer patients (43,58,127), since music can lower cancer-treatment biomarker IL-6 (94,112,145) while EE and physical exercise can reduce tumor size and increase lifespan in cancer animal models (127,128,146). Other clinical opportunities to combine non-pharmacological modalities with pharmaceutical drugs and biologics include Parkinson's and Alzheimer's diseases (21), asthma (147), arthritis (148) and affective disorders (143,149).…”
Section: Translational Implications Of Studying Enriched Environmentmentioning
confidence: 99%